Shifting HPV-cancer burden: from cervical cancer to oropharyngeal cancer - Volpi, Connor R.; Giuliano, Anna R.; Morais, Edith; Felsher, Marisa (Infectious agents and cancer, 2025)
Purpose This study aims to explore the contrasting trends of decreasing cervical cancer (CC) rates among women and increasing oropharyngeal cancer (OPC) rates among men. Methods The analysis examines public health initiatives, including CC screening programs and HPV vaccination efforts, alongside the changing epidemiology of OPC. Results Declines in CC incidence are attributed to improved screening and HPV vaccination. Conversely, OPC rates are rising among men, linked primarily to HPV infection and lack of established screening programs. Data indicate a higher OPC burden in men compared to CC in women in several countries. Conclusion Addressing the rising OPC trend requires a multifaceted approach, including gender-neutral HPV vaccination, the development of OPC screening methods, and increased public awareness. Sustained efforts in HPV-related cancer prevention are crucial to mitigate these opposing trends.